As barreiras para adoção de práticas de logística reversa: survey em empresas brasileiras construtoras de edifícios - Correia, José Manuel Ferreira (2017)
The Brazilian government promulgated the national solid waste policy through law 12,305 / 2010, which encourages construction industries to adopt Reverse Logistics practices for the management of solid waste. However, construction industries suffer barriers to the implementation of Reverse Logistics. The objective of this research is to evaluate the barriers that impede the more effective adoption of Reverse Logistics practices in Brazilian construction industries. The research method used was a bibliometric and systematic review about the theme Reverse Logistics in civil construction to identify the variables for the elaboration of the research instrument. The face test was then performed with three specialists for validation. Subsequently, the survey method was applied (104 questionnaires). The results of this study add in the existing researches, through a multivariate analysis of the data making possible the managerial decision making and confirmed that the barriers impede the more effective adoption of Reverse Logistics practices. These industries have difficulties in investing in infrastructure resources, in quality management system (ISO 9001) and In the training of its employees, which affects the understanding and the organizational understanding for the elaboration of projects, which include the principles of Reverse Logistics, such as: the study of collection points, life cycle analysis and mass balance evaluation. With this there is no the development of organizational structure, which compromises the hiring of specialized managers and a better evaluation of logistics operators. In addition, the lack of knowledge about obtaining credit lines and government regulatory incentives increases its operational costs and generates an unfavorable organizational culture. On the other hand, the adoption of Reverse Logistics practices promotes the improvement of its processes of selective demolition and waste management. In this way the industries obtain economic, environmental and social gains by the best use of recovered materials and recycled and by the decrease of the generated amount of waste for the discard.